2010
DOI: 10.1016/j.taap.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic injury in hepatic alcohol dehydrogenase-deficient deer mice after subchronic exposure to ethanol

Abstract: Pancreatitis caused by activation of digestive zymogens in the exocrine pancreas is a serious chronic health problem in alcoholic patients. However, mechanism of alcoholic pancreatitis remains obscure due to lack of a suitable animal model. Earlier, we reported pancreatic injury and substantial increases in endogenous formation of fatty acid ethyl esters (FAEEs) in the pancreas of hepatic alcohol dehydrogenase (ADH)-deficient (ADH−) deer mice fed 4% ethanol. To understand the mechanism of alcoholic pancreatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 58 publications
7
61
0
Order By: Relevance
“…In our previous study, we found significant deaths in hepatic alcohol dehydrogenase (ADH)-deficient (ADH − ) deer mice vs. hepatic ADH normal (ADH + ) deer mice fed 4% ethanol daily for 2 months (Bhopale et al, 2006). Therefore, in these studies, we reduced ethanol exposure to 3.5% in the diet, as no significant deaths were found at this concentration of ethanol fed daily for 2 months (Kaphalia et al ., 2010). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we found significant deaths in hepatic alcohol dehydrogenase (ADH)-deficient (ADH − ) deer mice vs. hepatic ADH normal (ADH + ) deer mice fed 4% ethanol daily for 2 months (Bhopale et al, 2006). Therefore, in these studies, we reduced ethanol exposure to 3.5% in the diet, as no significant deaths were found at this concentration of ethanol fed daily for 2 months (Kaphalia et al ., 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Hepatic ADH − deer mice are naturally deficient in hepatic class I ADH and more susceptible to ethanol toxicity as compared to ADH + deer mice (Bhopale et al ., 2006; Kaphalia et al ., 2010). Multiple genes code for hepatic ADH in deer mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bound FAEEs can be accumulated and may serve as potential uncouplers of the mitochondrial oxidative phosphorylation, as demonstrated with ethyl oleate (Lange, 1982;Laposata, 1998;Lange & Sobel, 1983). Alternatively, FAEEs can stimulate apoptosis in pancreatic acinar cells with elevated calcium-related toxicity with decreased ATP synthesis (Criddle et al, 2006(Criddle et al, , 2004Kaphalia et al, 2010). On the other hand, recent results demonstrated that exogenous ethyl esters of n-3 fatty acids including eicosatetrapentaenoic acid and docosahexaenoic acid show protective effects against obesity-related metabolic syndrome (Depner, Philbrick, & Jump, 2013;Mori et al, 1999;Pérez-Echarri et al, 2008, 2009Pérez-Matute, Pérez-Echarri, Martínez, Marti, & Moreno-Aliaga, 2007;Spencer et al, 2013).…”
Section: Role Of Nonoxidative Alcohol Metabolism In Liver Diseasementioning
confidence: 99%
“…A strain of deer mice (Peromyscus maniculatus) naturally deficient in ADH [180] has been used to study various aspects of ethanol metabolism [181,182]. In animals fed a 4% ethanol diet for 60 days, these studies demonstrated increased nonoxidative metabolism of ethanol to fatty acid ethyl esters in ADH-/-versus WT animals, in addition to increased mortality and histological changes to the liver and pancreas.…”
Section: Adh (Knock-out) Modelsmentioning
confidence: 99%